EVALUASI KESESUAIAN LAHAN TANAMAN KACANG TANAH DAN JAGUNG DI KAMPUNG GURINDA JAYA DISTRIK JAGEBOB KABUPATEN MERAUKE - Martinus Kamunop; Yosefina Mangera; Parjono Parjono (Faculty of Agriculture, Musamus University, 2021)
The purpose of this study was to evaluate the land suitability of peanuts and corn in Gurinda Jaya Village, Jagebob District, Merauke Regency. The research was carried out from July 2020 to August 2020. The research location was carried out in Gurinda Jaya Village, Jagebob District, Merauke Regency. The materials used in this research are: Gurinda Jaya Village Map, 10 year rainfall data (2011-2020), humidity data, temperature data, morphological data of Gurinda Jaya village, soil samples. The suitability parameters for Peanut and Corn include temperature, dry month, rainfall, soil drainage, texture, CEC, wet saturation, pH, C-Organic, salinity, total alkalinity-N, P2O5, K2O, land suitability class consists of class S1 (very suitable), S2 (moderately suitable), S3 (marginally suitable), N1 (not suitable). The results showed that peanut plants in paddy fields/moorlands, scrub lands and dry land forests obtained marginal land suitability class (S3) with limiting factors for nutrient retention (f) and available nutrients (n) for paddy fields/fields and dryland forests. , while the limiting factors in bushland are rooting media (r), nutrient retention (f), and available nutrients (n). Land suitability class for maize, on marginally suitable paddy fields/moor (S3) with limiting factors for nutrient retention (f), available nutrients (n), for bushland and dry land forests are not suitable at this time (N1) with limiting factors available nutrients (n). Basically, the existing limiting factors can be improved by fertilizing and liming.